Smaller babies at risk: birth weight impacts neonatal survival status in Silte zone, Central Ethiopia. A survival analysis of prospective cohort study - Jemal, Musa; Kemal, Abdurezak; Mohammed, Bekri; Bedru, Delwana; Kedir, Shemsu (Frontiers in Pediatrics, 2024)
Introduction: Globally, 2.4 million neonates died in the first month of life by 2019, approximately 6,700 neonatal deaths every day. Ethiopia is 4 th leading country among the top 10 countries with the highest number of neonatal death. Yet, there are few prospective studies on neonatal mortality in the central region of Ethiopia. Hence, in order to develop evidence-based, locally tailored intervention strategies, it is necessary to evaluate neonatal survival status and mortality predictors, including birth weight. Therefore, the current study aims to assess survival status and factors predicting survival of neonates in Silte zone, Ethiopia.Methods: An institution based prospective cohort study design was employed from May 01 to July 30, 2022. Data were collected from term neonates enrolled by their order of health facility visit then followed by data collectors in their home. Data were analyzed using STATA version 14.1. Neonatal survival was presented using Kaplan-Meyers survival curve. Crude and adjusted association was evaluated using cox-proportional hazard model and presented with 95% confidence interval and P value <0.05 was used to declare statistical significance.Result: 1080 term neonates were followed for a total of 27643.6 neonatal day. The study showed a 95% cumulative probability of surviving the neonatal period. The incidence rate of neonatal death was 2.02 per 1000 neonatal days. Maternal history of neonatal death (AHR=4.03; 95%CI: